The transformational possibilities of a peer education program to address child marriage in Nepal. Issue 7 (3rd October 2022) - Amigó, María Florencia; Gurung, Sandeep
ABSTRACT: Peer education has been a popular strategy in health promotion campaigns willing to reach large populations at manageable costs. The modality has been critiqued for engaging a poorly trained and cheap workforce; however, it is still broadly utilised in development programs. By focusing on qualitative data obtained from program stakeholders for the final evaluation of an intervention to address child marriage in Nepal that made use of peer educators, this article explores how properly supported peer education programs may lead to women's empowerment, activism, and cultural change.